2017
DOI: 10.1103/physreve.95.013101
|View full text |Cite
|
Sign up to set email alerts
|

Bifurcation induced by the aspect ratio in a turbulent von Kármán swirling flow

Abstract: We evaluate the effect of two experimental parameters on the slow dynamics of a Von-Kármán swirling flow driven by two propellers in a closed cylinder. The first parameter is the inertia momentum of the propellers, and the second parameter is the aspect ratio, i.e. the distance between the propellers H divided by the diameter D. We use a cell with a fixed diameter D but where the distance between the propellers can be turned continuously and where the inertia from the propellers can also be changed using diffe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Conditioning the dataset on the two states, we have reconstructed corresponding mean flows and demonstrated a rotation of π/2 around the axis of rotation. Consequently, the present bistability is different from those observed in similar flows produced in a cylindrical vessel for which the different states mirror each other in a reflexion about the midplane z = 0 [16][17][18]25]. Further work is needed to fully characterize the reversals and their temporal dynamics and to test modeling approaches typically used in confined flows or more generally techniques pertaining to turbulent multi-stability such as [16,26,27].…”
Section: Discussionmentioning
confidence: 67%
“…Conditioning the dataset on the two states, we have reconstructed corresponding mean flows and demonstrated a rotation of π/2 around the axis of rotation. Consequently, the present bistability is different from those observed in similar flows produced in a cylindrical vessel for which the different states mirror each other in a reflexion about the midplane z = 0 [16][17][18]25]. Further work is needed to fully characterize the reversals and their temporal dynamics and to test modeling approaches typically used in confined flows or more generally techniques pertaining to turbulent multi-stability such as [16,26,27].…”
Section: Discussionmentioning
confidence: 67%
“…When the fluid is in a laminar regime, the flow created can generate coherent structures that have been analyzed numerically and experimentally [10,11]. In the turbulent regime, the global recirculation can destabilize, and a rich dynamics appears [8,9,12,13]. Apart from the interest as a fundamental problem of fluid mechanics, the presence of instabilities on these flows can affect other processes: these flows have been used experimentally to generate the dynamo action [14,15], and it has been observed that the presence of instabilities can significantly affect the threshold of this effect [16,17].…”
Section: Introductionmentioning
confidence: 99%